Pengaruh Pembelajaran Taktikal Permainan Bola Voli terhadap Peningkatan Keterampilan Gerak Dasar Siswa SMP Negeri 2 Makassar - Sahabuddin (PT. Penerbit Tiga Mutiara, 2025)
This study aims to evaluate the effectiveness of volleyball game–based tactical learning in improving the fundamental movement skills of students at SMP Negeri 2 Makassar. The research employed a quasi-experimental method with a non-equivalent control group design, involving 40 seventh-grade students divided into an experimental group (n=20) and a control group (n=20). The experimental group received tactical game–based learning focused on understanding game situations, decision-making, and applying tactical concepts within the context of play. In contrast, the control group followed conventional technique-based instruction emphasizing repetition of basic movements. Measurement of fundamental movement skills, particularly manipulative skills in volleyball, was conducted using the Fundamental Movement Skills (FMS) test during the pretest and posttest stages. Data analysis was carried out descriptively and inferentially using paired-sample t-tests to identify changes within each group, as well as independent-sample t-tests to examine differences in improvement between groups at a significance level of 0.05. The results showed that both groups experienced significant improvement in fundamental movement skills. However, the improvement in the experimental group was statistically more pronounced than in the control group, accompanied by a large effect size indicating a strong impact of the treatment. These findings confirm that volleyball game–based tactical learning provides a more effective contribution to developing students’ fundamental movement skills compared to conventional instruction. Theoretically and practically, this study recommends the implementation of tactic-based approaches as more relevant, authentic, and competency-oriented learning strategies in physical education.